1999
DOI: 10.2307/3345490
|View full text |Cite
|
Sign up to set email alerts
|

A Description of Vocal Maturation among Fifth- and Sixth-Grade Boys

Abstract: The present study was designed to explore the idea that boys' voices may be changing earlier than indicated in previous research. Singing and speaking voices of fifth-grade (h = 56) and sixth-grade (h = 43) boys were categorized and compared with the Cooksey changing voice stages. Data consisted of grade in school, age in years, highest and lowest sung pitches, overall singing range, speaking pitches, and voice stage categorization. Results indicated an earlier voice change than in previous research. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 4 publications
5
41
0
Order By: Relevance
“…Barresi and Bless (1984) determined that tessitura was not a reliable measure of voice change, causing Cooksey (1984) to concede that "range is the single most important factor for delineating different stages of voice development" (p. 7). Various studies have verified the validity of Cooksey's stages (Cooksey, 1984;Cooksey, 1985;Cooksey & Welch, 1998;Groom, 1984;Killian, 1999). Also, Harries et al (1997) found that Cooksey's stages correlated with Tanner's stages of development.…”
Section: British Male Voice Change Theoriesmentioning
confidence: 96%
See 4 more Smart Citations
“…Barresi and Bless (1984) determined that tessitura was not a reliable measure of voice change, causing Cooksey (1984) to concede that "range is the single most important factor for delineating different stages of voice development" (p. 7). Various studies have verified the validity of Cooksey's stages (Cooksey, 1984;Cooksey, 1985;Cooksey & Welch, 1998;Groom, 1984;Killian, 1999). Also, Harries et al (1997) found that Cooksey's stages correlated with Tanner's stages of development.…”
Section: British Male Voice Change Theoriesmentioning
confidence: 96%
“…His research largely focused on middle school aged boys since, during his early studies, it was believed that most males underwent maturation during the middle school years, but as his investigations continued he began to notice trends in the earlier onset of the male voice change (Cooksey, 1984). Other researchers have found evidence of earlier trends in male vocal mutation as well (Karr, 1988;Killian, 1999;Moore, 1995;Rutkowski, 1984). Rutkowski (1984) found that 50% of the 6 th grade male students in her study could be classified as changing, whereas Killian (1999) concluded that approximately 80% of the 6 th grade male students in her study had entered Cooksey's voice change stages.…”
Section: Need For the Studymentioning
confidence: 99%
See 3 more Smart Citations